HEPATITIS C VIRUS GENOTYPING IN SULAIMANI GOVERNORATE - Kareem, Banaz Omar; Salih, Gaza Faraj (European Scientific Journal, ESJ, 2014)
To determine the HCV genotypes among HCV-infected patients in Sulaimani governorate Kurdistan region- Iraq, 76 blood samples were collected (60 samples were positive and 16 samples were negative for anti- HCV antibody) from different groups the samples comprised: 21 (27.63%) hemodialysis patients, 38 (50%) thalassemia patients, 4 (5.26%) cancer patients, 3 (3.95%) gastritis patients, 1 (1.32%) hemophilia patient and 9 (11.84%) blood donors. RT- nested PCR analysis showed that 35 (46.05%) were positive and 41 (53.95%) were negative for HCV-RNA. Amplification of 5’UTR of HCV-RNA positive samples were done by RT- nested PCR; the amplified product was purified and sequenced in IBL laboratory in Vienna. The sequenced samples were BLAST on NCBI online website. The alignment sequence and phylogenetic analysis used CLUSTAL W online software version 1.83 of 24 samples showed that genotype 1 was the predominant genotype among HCV infected patients in Sulaimani governorate, with an overall of (87.5%) patients. Genotype 2 was found in (8.3%), and genotype 4 was seen in (4.2%) patients. The study aimed to detect the HCV- RNA in the blood samples by RTnested PCR analysis and sequencing in order to determine the HCV genotypes in Sulaimani governorate-Kurdistan-Iraq.